Transformation of Music Structure and Form in Marriage Ceremony of Simalungun Community in Jakarta - Purba, Hebert Lasrohadin (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2024)
This paper is a study of the transformation of the structure and form of music in the marriage ceremony of the Simalungun community in Jakarta. With changes in the way of working and dynamic cultural thinking, the Simalungun community in Jakarta "negotiated" with the presence of Uning-uningan and wind music (keyboard), despite the impact of killing traditional music (Gonrang) which has become a musical identity so far. The focus of this research is to review the sound changes from the Gonrang Sidua-Dua music structure to uning-uningan or Batak toba music using Simon Waters's "Acoustic to Electroacoustic" theory as an analysis tool. The method of this research is qualitative, namely by field observation of Simalungun marriage places, interviews with Simalungun traditional leaders, and recording documentation. The use of keyboards in Simalungun wedding customs in Jakarta shows a change from traditional gondang sounds to gondang sounds in the keyboard and changes in the sound of uning-uningan which was previously gondang hasapi (traditional Toba Batak musical instrument) after being combined with brass bands or wind music and the use of sound systems resulting in changes in acoustic sound to electroacoustic. Besides the difficulty of the existence of gondang music from the traditional side, the value of modernization has benefits such as preservation and revitalization of traditional music, one of which is through the institution of marriage, namely by practicing editing technology and sampling styles or rhythms that are widely used today such as Gondang tor-tor, Rumba odak-odak, Patam- patam Karo, and Simalungun rayat on the Keyboard. The results of this research show that music technology using keyboards in the uning-uningan group through the process of editing styles and sounds is one way to preserve traditional Simalungun music which is gradually becoming extinct.